Atlas of Esophageal Surgery - Herbella, Fernando A. M.; Patti, Marco G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This Atlas focuses on surgical techniques used to treat the entire spectrum of esophageal diseases. Surgical (3z(Bpearls(3y (Band tips on how to select and perform the correct operation are included and based both on evidence-based data and the experience of the Editors. Step-by-step descriptions of operative and endoscopic procedures in esophageal surgery are provided. Each chapter describes the current indications, perioperative management strategies, and a detailed operative approach with relevant technical considerations. The description of approaches and surgical techniques used in esophageal surgery are outlined in an easily understandable manner for the specific target audience. This book is written by world-class internationally renowned esophageal surgeons and gastroenterologists.s
1. History of esophageal surgery. Herbella FAM -- 2. Radiology for esophageal diseases. D$1 (BIppolito Giuseppe -- 3. Endoscopy: from diagnosis to treatment. Ferri L -- 4. Esophageal function tests. Herbella FAM -- 5. Laparoscopic operations for gastroesophageal reflux disease. Patti MG -- 6. Laparoscopic paraesophageal hernia repair. Oleynikov D -- 7. Laparoscopic Heller myotomy with Dor fundoplication. Patti MG -- 8. POEM. Hungness E -- 9. Zenker$1 (Bs diverticulum. From the open to the endoscopic approach. Ujiki M -- 10. Epiphrenic diverticulum. Velanovich V -- 11. Trans-hiatal esophagectomy. Posner MC -- 12. Roux-en-Y bypass for GERD and morbid obesity. Prachand V -- 13. Ivor Lewis esophagectomy. Low D -- 14. Hybrid esophagectomy. Patti MG -- 15. Minimally invasive esophagectomy. Molena D.s
Keywords: Gastroenterology; Surgery; Gastroenterology; General Surgery; Esophageal Diseases -- surgery; Digestive System Surgical Procedures -- methods; Esophagus -- surgery; Atlases